New York-Paris : Whitman, Baudelaire, and the Hybrid City - Katsaros, Laure (University of Michigan Press, 2012)
A comparison of the mid-19th-century city in the poetry of Walt Whitman and Charles Baudelaire and their responses to the inescapable push of modernization.